The Impact of Tourist Interaction with Infrastructure and Per Capita GRDP on Hotel and Restaurant Taxes - Miranda Naya Elvaretta; Ferry, Prasetyia (Journal of Development Economic and Social Studies, 2026)
This study examines the effects of per capita GRDP and infrastructure on hotel and restaurant tax revenue in East Java Province during the 2015–2023 period, as well as the role of interactions with the number of tourists. Using secondary data and a quantitative approach, this study employs Fixed-Effects Panel Regression and Moderated Regression Analysis (MRA). The results indicate that per capita GRDP has a positive and significant effect on hotel and restaurant tax revenue, while road length only significantly affects restaurant tax revenue. Transportation hubs do not show a significant effect, and the number of tourists only interacts significantly with road length. These findings suggest that strengthening road infrastructure and enhancing local economic capacity are more effective in optimizing tax revenue than simply increasing the number of tourists, thereby providing insights for policy planning and the development of sustainable regional tourism.